2002
DOI: 10.1007/bf02344218
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of the Hemopump as a cardiac assist device

Abstract: A dynamic model was developed for a Hemopump that withdraws blood from the left ventricle and discharges it to the aorta through a miniature axial-flow pump. Incorporation of the Hemopump model in a previously established model for the canine circulatory system enabled the effects of the Hemopump on various haemodynamic variables of the circulatory system to be studied, and the benefit of the Hemopump to the failing heart was investigated. In addition, the influence of the physiological status of the right ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The simplest VAD representation is a prescribed flow function. 15 A more sophisticated method was to construct an equation containing the variables of pump flow, pressure difference across the pump, and the pump rotation speed, matching the experimental measurements of the pump characteristics using regression analysis, while the pump rotor dynamics were either neglected 1,3,4,13,14,30 or modeled considering the various momenta acting on the rotor. 7,11,32 In this article, the pump is modeled by constructing a relationship Q = Q(DP, x) to describe the characteristic pressure-flow relation, while the rotor dynamics of the pump are assumed to be ideal and not included.…”
Section: Model Of the Impeller Pump Vadmentioning
confidence: 99%
“…The simplest VAD representation is a prescribed flow function. 15 A more sophisticated method was to construct an equation containing the variables of pump flow, pressure difference across the pump, and the pump rotation speed, matching the experimental measurements of the pump characteristics using regression analysis, while the pump rotor dynamics were either neglected 1,3,4,13,14,30 or modeled considering the various momenta acting on the rotor. 7,11,32 In this article, the pump is modeled by constructing a relationship Q = Q(DP, x) to describe the characteristic pressure-flow relation, while the rotor dynamics of the pump are assumed to be ideal and not included.…”
Section: Model Of the Impeller Pump Vadmentioning
confidence: 99%
“…In our previous report (LI et al, 2002), we have shown that, by operating the Hemopump in a synchronous mode, i.e. at a higher speed during systole and a lower speed during diastole, both aortic flow and aortic pressure show a higher degree of pulsation, resembling more closely natural waveforms.…”
Section: Discussionmentioning
confidence: 93%
“…1 shows the computer model used in this study. The details of the model have been described in a previous paper (LI et al, 2002). In brief, the entire model contained a canine cardiovascular model and a dynamic Hemopump model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forthese reasons we improved our computerm odelo ft he cardiovascular system [3][4][5] with aH emopump model [6][7][8]. This rotary pump can be used as left ventricular assist device (LVA D) or as right ventricular assist device (RVA D).Inour model the assistance works as RVAD: it takesbloodfrom the right ventricle andejectsitinto the pul-monaryartery.…”
Section: Introductionmentioning
confidence: 99%